A Game of Hare & Hounds : An Operational-level Command Study of the Guilford Courthouse Campaign, 18 January-15 March 1781 - Skinner, Harold, Jr., 1966- (Book collections on Project MUSE., 2021)
"A Game of Hare & Hounds: An Operational-level Command Study of the Guilford Courthouse Campaign, 18 January-15 March 1781 provides a systematic analysis of this key battle in the American Revolution. This guide is intended for the instructor/facilitator, the individual who guides the execution of an applied history training event"--